TGFβ signaling regulates epithelial–mesenchymal plasticity in ovarian cancer ascites-derived spheroids. Issue 3 (8th December 2015) - Rafehi, Samah; Valdes, Yudith Ramos; Bertrand, Monique; McGee, Jacob; Préfontaine, Michel; Sugimoto, Akira; DiMattia, Gabriel E; Shepherd, Trevor G
Abstract : Epithelial–mesenchymal transition (EMT) serves as a key mechanism driving tumor cell migration, invasion, and metastasis in many carcinomas. Transforming growth factor-beta (TGFβ) signaling is implicated in several steps during cancer pathogenesis and acts as a classical inducer of EMT. Since epithelial ovarian cancer (EOC) cells have the potential to switch between epithelial and mesenchymal states during metastasis, we predicted that modulation of TGFβ signaling would significantly impact EMT and the malignant potential of EOC spheroid cells. Ovarian cancer patient ascites-derived cells naturally underwent an EMT response when aggregating into spheroids, and this was reversed upon spheroid re-attachment to a substratum. CDH1 /E-cadherin expression was markedly reduced in spheroids compared with adherent cells, in concert with an up-regulation of several transcriptional repressors, i.e., SNAI1 /Snail, TWIST1/2, and ZEB2 . Treatment of EOC spheroids with the TGFβ type I receptor inhibitor, SB-431542, potently blocked the endogenous activation of EMT in spheroids. Furthermore, treatment of spheroids with SB-431542 upon re-attachment enhanced the epithelial phenotype of dispersing cells and significantly decreased cell motility and Transwell migration. Spheroid formation was significantly compromised by exposure to SB-431542 that correlated with a reduction in cell viability particularly in combination with carboplatin treatment. Thus, our findings are the first to demonstrate that intact TGFβ signaling is required to control EMT in EOC ascites-derived cell spheroids, and it promotes the malignant characteristics of these structures. As such, we show the therapeutic potential for targeted inhibition of this pathway in ovarian cancer patients with late-stage disease.